GLUL Promotes Cell Proliferation in Breast Cancer. Issue 8 (21st April 2017) - Wang, Yanyan; Fan, Shaohua; Lu, Jun; Zhang, Zifeng; Wu, Dongmei; Wu, Zhiyong; Zheng, Yuanlin
ABSTRACT: Glutamate‐ammonia ligase (GLUL) belongs to the glutamine synthetase family. It catalyzes the synthesis of glutamine from glutamate and ammonia in an ATP‐dependent reaction. Here, we found higher expression of GLUL in the breast cancer patients was associated with larger tumor size and higher level of HER2 expression. In addition, GLUL was heterogeneously expressed in various breast cancer cells. The mRNA and protein expression levels of GLUL in SK‐BR‐3 cells were obviously higher than that in the other types of breast cancer cells. Results showed GLUL knockdown in SK‐BR‐3 cells could significantly decrease the proliferation ability. Furthermore, GLUL knockdown markedly inhibited the p38 MAPK and ERK1/ERK2 signaling pathways in SK‐BR‐3 cells. Thus, GLUL may represent a novel target for selectively inhibiting p38 MAPK and ERK1/ERK2 signaling pathways and the proliferation potential of breast cancer cells. J. Cell. Biochem. 118: 2018–2025, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Higher expression of GLUL in the breast cancer patients was associated with larger tumor size and higher level of HER2 expression. GLUL may represent a novel target for selectively inhibiting p38 MAPK and ERK1/ERK2 signaling pathways and the proliferation potential of breast cancer cells.